Thalictrum nanhuaense (Ranunculaceae), a new species from central Yunnan, China - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2021)
Thalictrum nanhuaense (Ranunculaceae), a new species from Nanhua in central Yunnan, China, is here illustrated and described. The new species is similar to T. fargesii in habit and having larger sepals up to 4 mm long and persistent at anthesis and straight styles, but differs by its succulent and tuberose (vs. fibrous and slender) roots, filiform (vs. clavate) filaments, point-like (vs. oblong and narrowly winged) stigmas, and subulate-terete (vs. lunate-fusiform) achenes.